Case report: Successful induction of buprenorphine in medically complex patients concurrently on opioids: a case series at a tertiary care center - Shelton, Thomas; Nama, Sharanya; Hall, Orman; Williams, Margaret (Frontiers in Pharmacology, 2024)
Effective pain management is essential for optimal surgical outcomes; however, it can be challenging in patients with a history of opioid use disorder (OUD). Buprenorphine, a partial opioid agonist, is a valuable treatment option for patients with OUD. Initiating buprenorphine treatment in patients concurrently taking opioids can be complex due to potential adverse outcomes like precipitated withdrawal. Evolving guidelines suggest there are benefits to continuing buprenorphine for surgical patients throughout the perioperative period, however situations do arise when buprenorphine has been discontinued. Typically, in this scenario patients would be restarted on buprenorphine after they have fully recovered from post-surgical pain and no longer require opioids for pain control. Unfortunately, holding MOUD may expose the patient to risks such as opioid induced respiratory depression or addiction relapse. In this case series, we discuss a novel method to restart buprenorphine in small incremental doses, known as micro-dosing, while the patient is still taking opioids for pain. We will present two complex clinical cases when this method was used successfully at a tertiary care hospital system.